FOTO KATALOG UNTUK BRANDING PRODUK UMKM CEMAL CEMIL CHIKA DI KELURAHAN GUNUNG ANYAR - Calvin, Calvin; Evanthi, Ayundha (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
Product photos are images taken to visually show potential buyers how the appearance and characteristics of the product offered. This activity aims to illustrate the product branding process of the Cemal Cemil Chika MSME catalog photo in Gunung Anyar Village carried out by the Real Working Group (KKN) Group 87 UPN Veteran East Java. The method of conducting this research involves observation, interviews, counseling, and product photo branding training to MSMEs Cemal Cemil Chika. The results of this study show that through the implementation of product photo branding methods, the photo catalog of MSMEs Cemal Cemil Chika can be significantly improved. Attractive product photos manage to attract the interest of potential customers more effectively. The use of proper photography techniques, good lighting, and attractive visual composition has increased the visual appeal of product photo catalogs.